Uji Efektivitas Antiinflamasi Sediaan Krim Kombinasi Ekstrak Rimpang Kencur (Kaempferia galanga L.) Dan Daun Srikaya (Annona squamosa L.) Pada Tikus Yang Diinduksi Karagenin - Akmal Aziz; Galih Samodra; Sunarti Sunarti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Inflammation is the body's response when it experiences injury, infection, antigen or cell damage, so it is a sign of something that is harmful to the body or disease. Galangal rhizomes (Kaempferia galanga L.) and Srikaya leaves (Annona squamosa L.) are plants that contain flavonoid compounds which have anti-inflammatory potential by inhibiting the enzymes cyclooxygenase and lipooxygenase. The aim of this research was to determine the effectiveness of a combination cream preparation of galangal rhizome extract and srikaya leaf extract as an anti-inflammatory. The various combinations used are a combination of 15 grams of kecur rhizome extract and 10 grams of srikaya leaf extract, 12.5 grams of srikaya rhizome extract and 12.5 grams of srikaya leaf extract, 10 grams of srikaya rhizome extract and 15 grams of srikaya leaf extract. The anti-inflammatory test uses 1% carrageenin induction of 0.1 ml, then the swelling that occurs is measured using a plastinometer. Based on the results obtained, a good anti-inflammatory power value was a combination of 15 grams of kencur rhizome extract with 10 grams of srikaya leaf extract with a value of 21.6216%. The results of the One Way Annova analysis obtained a p-value >0.05, which means there is no significant difference. So it can be concluded that various combinations of galangal rhizome extract and srikaya leaves are effective in mice induced by carrageenin. A post hoc Tuckey test was carried out on the AUC value, obtaining a p-value >0.05, so it can be concluded that there was no significant difference in the positive controls for formulas 1, 2 and 3.